Optimization strategies in the collection process to improve the operational efficiency of a private educational institution - Alfaro Rosas, Jorge Luis; Pozo Guevara, Katherine Milene; Angulo Vásquez, Carlos Leonardo; Cordova Cordova, Elder Harold; Alejandro Heredia, Luciana Pamela; Alvarez Tumbajulca, Xiomara Danitza (LACCEI, 2025)
This research aims to propose technological strategies to optimize the collections process at the private educational institution, which has a high delinquency rate of 31%, equivalent to a loss of S/ 23,520 annually. This situation directly impacts institutional liquidity, limiting educational investment and affecting service quality. Tools such as process analysis, Ishikawa diagram, FMEA matrix, and linear programming in LINGO were applied to identify critical causes such as lack of digital follow-up, poor communication, and absence of payment platforms. Four alternatives were evaluated, selecting the digitization of the process with automatic alerts and online payments due to its high economic impact, projected 10% reduction in delinquency, and recovery of up to S/ 32,000 annually. The proposal proved to be operationally and financially viable, with an ROI of over 900% and a return on investment in less than two months. It is concluded that the digital transformation of collections not only improves administrative efficiency but also strengthens institutional sustainability. Progressive implementation, staff training, and monitoring with key indicators are recommended